2019
DOI: 10.3390/app9163265
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Corrosion in AISI 304 Rolled Stainless Steel Welding at Different Deformation Levels

Abstract: This paper analyzes pitting corrosion at the weld zone and at the heat affected zone (HAZ) in AISI 304 rolled stainless steel welds. As the aforementioned material is one of the most frequently used types of stainless steel, it is needful to be aware of the mechanisms that lead to its deterioration, like corrosion, since it can cause failures or malfunction in a wide variety of products and facilities. For the experimental tests 1.5 mm thick AISI 304 stainless steel plates were welded and rolled to different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The chromium content drop under the passivity limit (11.5 wt %) near the grain boundaries leads to the sensitization of this material, which becomes susceptible to intergranular corrosion in aggressive environments [ 8 , 9 , 10 , 11 , 12 ]. Moreover, chromium depleted zones perform the preferential path for other local corrosion attacks and for crack propagation if under tensile stress [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromium content drop under the passivity limit (11.5 wt %) near the grain boundaries leads to the sensitization of this material, which becomes susceptible to intergranular corrosion in aggressive environments [ 8 , 9 , 10 , 11 , 12 ]. Moreover, chromium depleted zones perform the preferential path for other local corrosion attacks and for crack propagation if under tensile stress [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the relation between sensitization and the pitting corrosion susceptibility of austenitic SSs is the subject of numerous studies [ 13 , 14 , 19 , 20 , 21 , 22 , 23 ]. In addition to the effect of chromium-depleted zones, the authors of [ 14 , 20 , 21 ] presented the role of MnS inclusions on the pitting corrosion initiation of sensitized austenitic SSs.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the presence of chloride affects the electronic properties of reinforced concrete structure passivation films, and the austenitic SS reinforcements have better electronic and electrochemical properties than duplex SS reinforcements. Also, SS alloy can effectively enhance the slip-resistance, hardness, and corrosion resistance of ordinary stainless steel, so as to solve the problem of steel corrosion, but it was also affected by factors such as chloride ion concentration, corrosion inhibitor, and cold work levels [9][10][11][12][13]. Based on the research above, it can be concluded that the corrosion resistance of SS reinforced concrete structure is enough to increase by an order of magnitude compared with conventional carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…This is because in the case of localized corrosion the ORR that occurs on the cathode passive layer would promote the dissolution of metal (e. g. Fe metal becomes Fe 2 + ion). [16][17][18] In practice, additive elements such as Ti, Zr, Ni, etc., are usually added to stainless steels to improve its mechanical and other properties, however, the presence of these elements in the passive layer would also affect the ORR, but such an effect is usually overlooked. A systematic study of the alloying effects on the oxygen reduction activities on the Cr 2 O 3 surface remains unexplored in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Cr 2 O 3 is a well‐known component of the passive layer on stainless steels that can protect the metal from corrosion, where slow kinetics for the ORR reaction are desirable. This is because in the case of localized corrosion the ORR that occurs on the cathode passive layer would promote the dissolution of metal (e. g. Fe metal becomes Fe 2+ ion) [16–18] . In practice, additive elements such as Ti, Zr, Ni, etc., are usually added to stainless steels to improve its mechanical and other properties, however, the presence of these elements in the passive layer would also affect the ORR, but such an effect is usually overlooked.…”
Section: Introductionmentioning
confidence: 99%